Investigating the status of transgenic crops in Iran in terms of cultivation, consumption, laws and rights in comparison with the world - Abolfazl Baghbani-Arani; Mona Poureisa; Hossein Alekajbaf; Rezvan Karami Borz-Abad; Khodadad Khodadadi-Dashtaki (Scientific Reports, 2021)
Abstract Recently, there has been a development in transgenic technologies in many countries to meet nutritional needs of increasing worlds҆ population. However, there are some concerns about possible risks in the field of growing genetically modified (GM) food, such as threats of biodiversity and food allergies making their use a challenge. Therefore, the present study was conducted to investigate the economic effects and political scopes of GM foods in production sector and policies made by different countries in the world and Iran. Moreover, essential (practical and legal) solutions and guidelines were provided for production and consumption of GM foods, which are useful for governmental entities, Iranian politicians, and consumers' rights. The latest situation of transgenic crops in the countries with which Iran has the highest exchange of agricultural products (including Turkey, Pakistan, and the European Union (EU)) was also studied. Although, Iran has been one of leading Asian countries not only in the field of transfer of technical knowledge of genetic engineering, but also in development of the specialized knowledge of biosafety, and despite production of several transgenic plant lines by Iranian researchers, unfortunately no GM crop has obtained release and cultivation license except for GM rice that its growing process was banned after change of government. According to findings of this study, in Iran, growing and production process of GM crops does not follow the global trend owing to scientific and legal infrastructures.